Efeito da educação pré-primária no desempenho escolar - Markus, Nathalia de Pinho (2020)
This present work sought to measure the effect of pre-primary education on performance, measured from the grades of mathematics, of students in the 6th year of elementary school in public schools in the city of Recife, Pernambuco, Brazil, based on a survey conducted by Joaquim Nabuco Foundation in 2013. The methodology used was the Propensity Score Matching (PSM) with the purpose of comparing students who claim to have attended pre-primary school with a control group, composed of students who started school later.We sought to understand if the presence of parents and the characteristics of the school mitigated the effect. Specifically, a stratification analysis was performed using Quantile Treatment Effects (QTE).The results reveal that attending preschool has a positive impact on math performance, being even more effective for children with lower performance. Several econometric techniques were used to circumvent endogeneity problems. Oster’s sensitivity analysis (2019) indicated that there were no problems of omitted variables.